The American Counterculture of the Nineteen Sixties and Its Impact on the Promotion of Freedom in the United States - Bouchemal,Saad; Bensebaa ,Zineb Ikhlas; Kourdourli,Abdelkader (University of Ammar Theledji -Laghouat, 2021)
The present study aims to examine the impact of the counterculture of the 1960s on the promotion of freedom in the United States. To achieve this objective, the following questions are asked: To what extent did the counterculture of the 1960s affect freedom in the United States? What types of effects did the counterculture of the 1960s exert on American society and culture? What are the major domains of life in which the counterculture of the 1960s was most felt? How is the relationship between the counterculture and the promotion of freedom in the United States? In this study, an analytical-qualitative approach is adopted using data collection. The main results of the study are: First, there is a strong relationship between the counterculture of the 1960s and freedom in the United States; second, the counterculture of the 1960s did contribute to the promotion of freedom positively